AKTUALISASI FUNGSI KEIMIGRASIAN DALAM ASPEK KEAMANAN SEBAGAI UPAYA INTEGRAL PENANGANAN PANDEMI COVID-19 DI INDONESIA - Herman Suryokumoro (SASI, 2020)
This study aims to analyze the function of immigration in the security aspect, namely as a guard at the entrance to the territory of Indonesia during a pandemic. This function is of course very urgent considering that currently the spread of the Covid 19 virus is getting out of control, one of which is because there are still many foreigners entering Indonesian territory. The research method used is juridical normative, namely analyzing library materials or tracing documents related to the problem under study. The approach used is a statutory approach and a conceptual approach. The results showed that the actualization of the role of the immigration function during a pandemic can be seen from the aspect of immigration regulation and practices carried out by immigration checkpoints (ICP) throughout Indonesia. Meanwhile, the ICP has carried out its function as guardian of state security with the arrival of foreigners and closed several ICPs to limit immigration traffic. There is a significant difference in law enforcement during normal times and during the pandemic, namely the concessions given to foreign nationals in the form of changing overstay fees and deportation cannot be carried out. Deportation cannot be done because in general the person's home country also applies, so temporarily when foreigners who cannot return to their home countries stay in detention centers.